2017
DOI: 10.4209/aaqr.2016.07.0317
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Chemical Composition of Fine Particulates in Medium-Sized Urban Areas: A Case Study of Brazilian Cities

Abstract: The aim of this study was to characterize the inorganic chemical composition of fine inhalable atmospheric particulate matter (PM 2.5 ) in medium-sized cities in Brazil. These cities account for a significant proportion of the population and are growing at rates above the national average, thereby demonstrating the importance of carefully analysing the possible impact of such growth on air quality over the coming decades. In 2013 and 2014, this study collected PM 2.5 samples from sites in the cities of Londrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 60 publications
3
10
4
1
Order By: Relevance
“…Mean PM 2.5 concentrations ranged from 15.0 to 25.5 µg m −3 , from 10.1 to 37.2 µg m −3 , and from 6.5 to 29.3 µg m −3 in winter, spring, and summer, respectively. Beal et al 50 found mean PM 2.5 values of 4.4 µg m −3 during summer and 10.3 µg m −3 in winter for the city of Londrina.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Mean PM 2.5 concentrations ranged from 15.0 to 25.5 µg m −3 , from 10.1 to 37.2 µg m −3 , and from 6.5 to 29.3 µg m −3 in winter, spring, and summer, respectively. Beal et al 50 found mean PM 2.5 values of 4.4 µg m −3 during summer and 10.3 µg m −3 in winter for the city of Londrina.…”
Section: Resultsmentioning
confidence: 98%
“…Beal et al 50 reported a decrease in the mass concentration of PM as higher values of relative humidity were registered due to the wet deposition of the pollutants, whereas higher temperature values caused an increase in the mass concentration of PM 2.5-10 . Total and respirable PM were negatively correlated with humidity and positively correlated with temperature 66 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 BC concentration was obtained from reflectance value, filter area and sample volume. 17 The conversion of the reflected light is inversely proportional to the light absorbed, which is a function of the quantity of absorbent material present in the sample. BC concentration is given in µg m -3 .…”
Section: Sampling and Analysismentioning
confidence: 99%
“…The inhaled dose of particles obtained in this study means an average inhaled dose considering the diversity of exposure conditions along voluntary workday, which are the real-world conditions people are usually exposed to in urban environments. Health effects associated with inhaled dose of particles may be higher when considering how variable the chemical composition can be and their toxicity, with metallic and organic compounds in their composition (Beal et al, 2017;Ham and Kleeman, 2011).…”
Section: Studies Performed Bymentioning
confidence: 99%